(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This writing presents part of the Master’s research in Arts Pedagogy carried out with incarcerated adolescents in compliance with educational standards in the Benevides Socio-Educational Care Unit (PA). The aim was to investigate the creative process of the show The Flight of Bird Boys, which was built from the automatic writing of the adolescents and based on the Theatre of the Oppressed. These texts present reflective powers of these young people who, with their unique life experiences and world views, invite us to get to know reality from the perspective of those within history.